Application of nanomedicine for crossing the blood–brain barrier: Theranostic opportunities in multiple sclerosis. (2nd September 2016) - Ghalamfarsa, Ghasem; Hojjat-Farsangi, Mohammad; Mohammadnia-Afrouzi, Mousa; Anvari, Enayat; Farhadi, Shohreh; Yousefi, Mehdi; Jadidi-Niaragh, Farhad
Abstract: Multiple sclerosis (MS) is an autoimmune neurodegenerative disease characterized with immunopathobiological events, including lymphocytic infiltration into the central nervous system (CNS), microglia activation, demyelination and axonal degeneration. Although several neuroprotective drugs have been designed for the treatment of MS, complete remission is yet matter of debate. Therefore, development of novel therapeutic approaches for MS is of a high priority in immunological research. Nanomedicine is a recently developed novel medical field, which is applicable in both diagnosis and treatment of several cancers and autoimmune diseases. Although there is a marked progress in neuroimaging through using nanoparticles, little is known regarding the therapeutic potential of nanomedicine in neurological disorders, particularly MS. Moreover, the majority of data is limited to the MS related animal models. In this review, we will discuss about the brain targeting potential of different nanoparticles as well as the role of nanomedicine in the diagnosis and treatment of MS and its animal model, experimental autoimmune encephalomyelitis.